Pelayanan Administrasi Kependudukan Di Desa Tahalupu Kecamatan Huamual Belakang Kabupaten Seram Bagia Barat - Umulia Hermanses; Aminah Aminah; Pieter S Soselisa (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
This research is a study that uses qualitative methods to determine and analyze Population Administration Services in Tahalupu Village, Huamual Belakang District, West Seram Regency. This research was conducted in Tahalupu Village, Huamual Belakang Subdistrict, West Seram Regency. Primary data collection was carried out through interviews with a number of informants who were directly involved in the administration service process. The results of this study describe that the quality of population administration services in Tahalupu Village is generally categorized as not good, this is evidenced by the main tasks of service employees who have not been carried out optimally because the facilities / infrastructure in the Tahalupu Village office, Huamual Belakang District, West Seram Regency are not adequate.